Speech energetic theory: its essence, present-day state and prospects of its research - Kalyta, A. A. (Cognition, Communication, Discourse, 2018)
On the basis of a multi-level modeling of the system of psychophysiological energy functioning in the communicant’s spiritual sphere the author advances the essence of speech energetic theory, its present-day status and perspectives of its future development. The paper presents the paradigmatic system of subordination of existing and potential directions and aspects in research of energetic processes in communication. The analysis of structural and energetic picture of speech generation and decoding enabled the author to set out methodological conditions of further studies within the scope of speech energetic theory.